Analisis dan Solusi Kemacetan Lalu Lintas di Simpang Bersinyal (Studi Kasus: Simpang Bersinyal Jl. Panglima Batur Kota Banjarbaru) - Munanjar, Muhammad Chairi; Jihan Alya Nabillah; Hafsha Yanti Siregar (Jurnal Serambi Engineering, 2026)
Banjarbaru as one of the strategic cities is experiencing rapid development. This development has an impact on increasing vehicle volume. One of the intersections that often experiences congestion is the signalized intersection on Jalan Panglima Batur, which connects the North Approach (Jalan Pangeran Suriansyah Ujung), the South Approach (Jalan Pangeran Suriansyah), and the West Approach (Jalan Panglima Batur Timur) and the East Approach (Jalan Panglima Batur). This study aims to analyze the performance of the signalized intersection of Jalan Panglima Batur using the MKJI method, 1997. The parameters analyzed include traffic volume, approach capacity, degree of saturation (DS), and level of service (Level of Service/LOS). The results of the analysis show that the East Approach (Jalan Panglima Batur) which has the worst degree of saturation and LOS values ​​compared to the other 3 intersection approaches has the same Level of Service (LOS) value, namely type F. This condition indicates that the intersection capacity is no longer able to accommodate the existing traffic volume, causing congestion, large delays, and long queues at all approaches. To improve intersection performance, improvements are needed, such as adjusting signal cycle times, widening lanes on approaches with the highest traffic volumes, and restructuring activities around the intersection that cause high side traffic, particularly in shopping areas.